2009
DOI: 10.1186/1751-0147-51-31
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormone receptors ERα and PR characterised by immunohistochemistry in the mare adrenal gland

Abstract: Background: Sex steroid hormone receptors have been identified in the adrenal gland of rat, sheep and rhesus monkey, indicating a direct effect of sex steroids on adrenal gland function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Protein localization of ER-␣, ER-␤, PR, EP2 and EP4 in uterine tissue was investigated by immunohistochemistry (IHC) using antibodies previously validated for the horse (Abd-Elnaeim et al, 2009;Alm et al, 2009;Ball et al, 2013;Parlevliet et al, 2006;Pearl et al, 2011). Endometrium and myometrium were fixed in 10% formalin for 24 h. After the 24 h fixation period, samples were dehydrated and embedded in paraffin.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Protein localization of ER-␣, ER-␤, PR, EP2 and EP4 in uterine tissue was investigated by immunohistochemistry (IHC) using antibodies previously validated for the horse (Abd-Elnaeim et al, 2009;Alm et al, 2009;Ball et al, 2013;Parlevliet et al, 2006;Pearl et al, 2011). Endometrium and myometrium were fixed in 10% formalin for 24 h. After the 24 h fixation period, samples were dehydrated and embedded in paraffin.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Likewise, the basal CORT pattern differed between intact and ovariectomized mares, suggesting that E2 may affect the adrenal function. Indeed, Alm et al [ 44 ] showed E2 receptors (ER) in cortex and adrenal medulla in ovariectomized mares, showing that the ovulatory dynamics could be the result in the same way of ACTH and CORT effects. Hence, it is possible to suggest the interaction among pre-ovulatory follicle, hypophysis, and adrenal synthesis during the ovulatory period.…”
Section: Discussionmentioning
confidence: 99%